2011
DOI: 10.1002/lary.21785
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of asymmetric facial growth with deviated nasal septum

Abstract: We demonstrate that there is a strong relationship between deviated nasal septum and facial growth asymmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 11 publications
1
60
1
3
Order By: Relevance
“…Many investigators have tried to determine whether there is a relationship between nasal septal deviation and facial asymmetry, and they demonstrated that there is a positive relationship between nasal septal deviation (NSD) and facial growth. [4][5][6]10,11 However, previous studies on the role of nasal septum in facial asymmetry have certain limitations, and controversy still exists over these studies. Previous studies have some limitations with respect to the evaluation.…”
mentioning
confidence: 98%
“…Many investigators have tried to determine whether there is a relationship between nasal septal deviation and facial asymmetry, and they demonstrated that there is a positive relationship between nasal septal deviation (NSD) and facial growth. [4][5][6]10,11 However, previous studies on the role of nasal septum in facial asymmetry have certain limitations, and controversy still exists over these studies. Previous studies have some limitations with respect to the evaluation.…”
mentioning
confidence: 98%
“…Morphological asymmetry in the cranial region can cover, among others, maxillary sinuses, frontal sinuses and asymmetric nasal septum. [31][32][33] Authors Wysocki et al came to the conclusion that, in humans, the ratio of the venous foramen's surface to the capacity of the cranial cavity is significantly lower than in animals. 34 It has been noted that asymmetry characterizes the size of the venous foramen for the cardiac veins, and it occurs more often in humans than in animals.…”
mentioning
confidence: 99%
“…The stuffed nose has an adverse effect on the development of the child. Also, it has been reported that nasal septal deformity has an important effect on the facial growth and development, especially in the first decade of life [27][28][29][30]. Surgical correction may be needed in order to alleviate these conditions.…”
Section: Introductionmentioning
confidence: 99%